Relasi Agama dan Sains - Muchasan, Ali (Ali Muchasan, 2020)
It cannot be denied that religion and science are two things that increasingly play an important role in human life. The development of science in the modern world does not mean a decline in the influence of religion in human life, as has been predicted in the secularization theory. The tendency of the strengthening of religion and science to attract the attention of many people, especially with regard to the relationship between the two. The number of religious views and doctrines that seem to contradict modern science theory allows the 'conflict' between religion and science. The case of the church's execution of Galileo in the 19th century and the long debate between proponents of the theory of evolution and creation theory became clear evidence of how mutually affirming conflicts have colored the relationship between religion and science. To avoid conflicts between religion and science, many people have tried to find the most suitable relationship model. In recent developments there has been a